2007
DOI: 10.1111/j.1551-2916.2007.02065.x
|View full text |Cite
|
Sign up to set email alerts
|

Near Infrared Absorption of Tungsten Oxide Nanoparticle Dispersions

Abstract: Homogeneous dispersions of reduced tungsten oxide and tungsten bronze nanoparticles with ternary additives Na, Tl, Rb, and Cs have been prepared in the wet process and examined for optical properties. The dispersions of reduced tungsten oxide and tungsten bronze nanoparticles are found to show a remarkable absorption of near infrared light while retaining a high transmittance of visible light. This property is highly suitable for solar control filters in automotive and architectural windows.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
87
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(90 citation statements)
references
References 12 publications
3
87
0
Order By: Relevance
“…When alkali metals are intercalated into the framework formed by corner-sharing WO 6 , the metal ions are believed to contribute their electrons to the conduction band of WO 3 , forming surface plasmon polariton of free electrons and introducing empty, higher sub-bands or states in the conduction band [5][6][7][8]. In this regard, tungsten bronze nanoparticles are attractive NIR absorbing materials, because of their unique and highly desirable optical properties, namely, strong absorption in the NIR wavelength range based on sub-band energy levels, and transparency in the visible wavelength range [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When alkali metals are intercalated into the framework formed by corner-sharing WO 6 , the metal ions are believed to contribute their electrons to the conduction band of WO 3 , forming surface plasmon polariton of free electrons and introducing empty, higher sub-bands or states in the conduction band [5][6][7][8]. In this regard, tungsten bronze nanoparticles are attractive NIR absorbing materials, because of their unique and highly desirable optical properties, namely, strong absorption in the NIR wavelength range based on sub-band energy levels, and transparency in the visible wavelength range [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The solid state reaction typically employs tungsten precursors and a heating process in a furnace at high temperatures over 500°C, while exposed to a gas flow consisting of a mixture of H 2 and N 2 to obtain products in the reduced state [11]. However, this conventional process is considered to be risky, because of the use of hydrogen gas.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the NIR absorption of tungsten bronze Cs x WO 3 is correlated with the plasmon resonance of free electrons, small polaron and interband transition [8]. In addition, the morphology, crystal structure and particle size of powders also play an important role in its NIR absorption performance and other optical-electrical properties of Cs x WO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, it has been reported that hexagonal cesium tungsten bronzes Cs x WO 3 exhibit higher visible transparency and excellent near infrared (NIR) absorption properties, and thus can be applied in some new fields such as transparent heat shielding glasses and solar filters [8][9][10][11][12][13], and photothermal ablation therapy [14] etc.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the bottomup synthesis and assembly of the nanocrystals enable for the development of unprecedented functional materials, structures, devices, and processes. Consequently, colloidal nanoparticles are employed in various fields: in optics, as optical filters [5,6], as lasers [7][8][9], or as LEDs [10]; in molecular biology, for labeling [11][12][13] or hyperthermia applications [14][15][16]; or in electronics [17]. The most appealing feature of the nanoparticles is the dependence of their physical properties on the size [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%